Analysis of Character Education Strengthening in Optimizing Work Culture of Vocational High School Students - Sri Mulyani; Muhammad Bakrun; Muhammad Sayuti (Jurnal Indonesia Sosial Sains, 2026)
Character education plays a strategic role in shaping the work culture of Vocational High School (SMK) students, but its integration with work culture based on the needs of the industrial world is still not optimal. This study aims to analyze the implementation of character education, the implementation of work culture, the effectiveness of strengthening character education on work culture, and the factors that influence the optimization of students' work culture in the Industrial Chemical Engineering major at SMK Negeri 2 Depok. The research used a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation with students, homeroom teachers, and the vice principal for student affairs during the period April–July 2025. Data were analyzed using thematic coding and validated through triangulation of sources, techniques, and time. The results indicate that character education is implemented systematically through values-based, habituation-based, collaborative, and exemplary approaches. The 5R work culture (ringkas, rapih, resik, rajin, and rawat) is consistently applied in intracurricular, co-curricular, and extracurricular activities, thus forming characters of discipline, honesty, resilience, and responsibility. The novelty of this study lies in the discovery of an integrated model for strengthening character education based on the 5R work culture, which has proven effective in improving the work readiness of vocational high school students in accordance with the demands of the industrial world.